4(x+2)-8(3x+6)=9(4x+8)

Simple and best practice solution for 4(x+2)-8(3x+6)=9(4x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)-8(3x+6)=9(4x+8) equation:


Simplifying
4(x + 2) + -8(3x + 6) = 9(4x + 8)

Reorder the terms:
4(2 + x) + -8(3x + 6) = 9(4x + 8)
(2 * 4 + x * 4) + -8(3x + 6) = 9(4x + 8)
(8 + 4x) + -8(3x + 6) = 9(4x + 8)

Reorder the terms:
8 + 4x + -8(6 + 3x) = 9(4x + 8)
8 + 4x + (6 * -8 + 3x * -8) = 9(4x + 8)
8 + 4x + (-48 + -24x) = 9(4x + 8)

Reorder the terms:
8 + -48 + 4x + -24x = 9(4x + 8)

Combine like terms: 8 + -48 = -40
-40 + 4x + -24x = 9(4x + 8)

Combine like terms: 4x + -24x = -20x
-40 + -20x = 9(4x + 8)

Reorder the terms:
-40 + -20x = 9(8 + 4x)
-40 + -20x = (8 * 9 + 4x * 9)
-40 + -20x = (72 + 36x)

Solving
-40 + -20x = 72 + 36x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36x' to each side of the equation.
-40 + -20x + -36x = 72 + 36x + -36x

Combine like terms: -20x + -36x = -56x
-40 + -56x = 72 + 36x + -36x

Combine like terms: 36x + -36x = 0
-40 + -56x = 72 + 0
-40 + -56x = 72

Add '40' to each side of the equation.
-40 + 40 + -56x = 72 + 40

Combine like terms: -40 + 40 = 0
0 + -56x = 72 + 40
-56x = 72 + 40

Combine like terms: 72 + 40 = 112
-56x = 112

Divide each side by '-56'.
x = -2

Simplifying
x = -2

See similar equations:

| 8+-2(a+-1)=5+a | | 4*(x+2)-8*(3x+6)=9*(4x+8) | | 8-2(a-1)=5+9 | | 4x+16+40=160 | | 8-2(a-1)=7+9 | | 3+7n=31 | | 4p-10=-2p+14 | | 15-3n=9 | | 9p-7=4p+23 | | 11-2(9-1)=4+9 | | -5(x-2)=15 | | 5x+40=8x | | 5p+5=2p+20 | | -4(x-6)+7=31 | | 5*x+7=3*x+19 | | u^2-7u+6=0 | | 6*x-24=2*x | | 9k^3+6k^2-5k+6=0 | | -6y+2=-4(2y+4) | | 6.5y=-63.7 | | -3+x-5=-13+9-8 | | 20X+10Y=-10X+15X-5Y | | 2x-5*2=25 | | 0=x^2+2x+6 | | x^5=0.4 | | 3x+40=50+2x | | 8-7x=37-14x | | 4x+6=-106-10x | | 26X^2-9X=0 | | x^4-13x^2+36= | | 5x+13=2x-23 | | 2x-7=33 |

Equations solver categories